1969
DOI: 10.1111/j.1365-2389.1969.tb01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and Morphology of Some Alpine Podzol Profiles

Abstract: Summary Some representative podzol profiles from an Alpine region are described. Their genesis is mainly a function of vegetation and drainage and is analysed by morphological, chemical, and mineralogical methods. The effect of soil management on profile development as governed by recent economic advances has been discussed. When meadows with brown soils that are preserved by careful management are abandoned, heather and bilberries start growing and podzolization processes begin. Illuviation horizons are forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…This result is in agreement with studies on litter decomposition by Schinner (1978) and Bouma et al (1969), who conducted studies in high alpine regions, and showed an increase in the above-ground organic horizons as a consequence of land-use changes. Humus type together with the factor of buffering capacity (Stützer 1998) is decisive for pedogenesis (Brahy et al 2000).…”
Section: Discussionsupporting
confidence: 94%
“…This result is in agreement with studies on litter decomposition by Schinner (1978) and Bouma et al (1969), who conducted studies in high alpine regions, and showed an increase in the above-ground organic horizons as a consequence of land-use changes. Humus type together with the factor of buffering capacity (Stützer 1998) is decisive for pedogenesis (Brahy et al 2000).…”
Section: Discussionsupporting
confidence: 94%
“…The 2:1 layers of HIV are thought to be stable, probably because the buffering capacity of interlayered materials is such that it can react with acid more easily than the 2:1 layers. Such a preferential dissolution of interlayered materials in 2:1 layers is widely observed in the surface horizons of acidic forest soils (Ross and Mortland, 1966;Bouma et al, 1969;Gjems, 1970;Hirai et al, 1989;Funakawa et al, 1992). In ID-S samples, small to negligible amounts of easily weathered minerals are present in soils from a tropical rainforest climate and relatively stable landscape conditions; this indicates limited potential for acid Fig.…”
Section: Transformation Of 2:1 Type Clay Mineralsmentioning
confidence: 95%
“…Although Lithic Humicryods and Haplocryods occur in lowelevation, temperate rainforests of southeast Alaska, they are especially predominant in alpine-subalpine ecosystems of the northern Appalachian Mountains, the North Cascades of Washington and British Columbia, the northern Rocky Mountains, the interior mountains of Alaska, and elsewhere in the Northern Hemisphere Norway (Ellis and Matthews, 1984;Caseldine and Matthews, 1987;Earl-Goulet et al, 1998), Switzerland (Bouma et al, 1969;Egli et al, 2001), the Carpathian Mountains of eastern Europe (Skiba, 2008), eastern and middle Siberia, Karelia, and the Kola Peninsula in Russia (Mazhitova, 1988;Pereverzev, 2007), and in the Japanese Alps (Shoji et al, 1982). However, the pedons reported by these investigators either were too deep or contained insufficient organic C in the Bhs horizon to be classified as Lithic Humicryods.…”
Section: Lithic Humicryods and Haplocryods As Disjunct Soilsmentioning
confidence: 99%